ISCHEMIA-MODIFIED ALBUMIN LEVELS AND DYNAMIC THIOL/ DISULFIDE BALANCE IN FEMALE PATIENTS WITH IRON DEFICIENCY ANEMIA (Applied Biological Research, 2023)
Iron deficiency anemia (IDA) affects about 20-30% of adults worldwide. The present study was aimed to determine the relationship between  ischemia-modified albumin (IMA) and dynamic thiol/disulfide balance in  female patients with IDA, and to reveal its effects on the development of  anemia and the organism. The study included a total of 88 individuals (48  patients/ 40 healthy). IMA levels and disulfide/thiol homeostasis were  measured by colorimetric and spectrophotometric methods. Total thiol  (TTL) levels were found significantly positively correlated with native thiol (NTL) values (r = 0.326, p
Keywords: Iron deficiency anemia; ischemia-modified albumin; oxidative stress; thiol/disulfide homeostasis